Tax compliance intention behavior among enforcement officers in Kulim Kedah - Kirttana, Sambathan (2023)
Tax compliance is crucial for governments worldwide to sustain revenue streams and support national development. However, despite efforts to optimize tax administration and promote voluntary compliance, challenges persist, particularly in countries like Malaysia. This study explores the factors influencing tax compliance intentions and behaviors among enforcement officers in Kulim, Kedah, Malaysia. Drawing on existing literature, this research addresses the gap in understanding the dynamics of tax compliance by examining the influence of attitudes and the presence of licensed tax agents on enforcement officers' compliance intentions. Additionally, it investigates the relationship between compliance intentions and actual behaviors. The significance of this study lies in its potential to inform policy and practice in tax administration, particularly in Malaysia, by identifying factors contributing to tax non-compliance and proposing strategies to enhance voluntary compliance. Through quantitative analysis and survey data, this research aims to contribute both theoretically and practically to the field of taxation, providing insights that can help tax authorities better understand and address tax compliance challenges. The scope of the study is limited to enforcement officers in Kulim, Kedah, given their unique context within the Malaysian tax system. The research methodology includes a quantitative approach involving the development of hypotheses, operational definitions, survey instruments, and data collection procedures. Overall, this study seeks to shed light on the complexities of tax compliance behavior and provide actionable insights for tax authorities to improve compliance strategies and ensure a fair and effective tax system.